2012
DOI: 10.1002/bdra.23099
|View full text |Cite
|
Sign up to set email alerts
|

Forebrain and hindbrain development in zebrafish is sensitive to ethanol exposure involving agrin, Fgf, and sonic hedgehog function

Abstract: BACKGROUND Ethanol is a teratogen that affects numerous developmental processes in the nervous system, which includes development and survival of GABAergic and glutamatergic neurons. Possible molecular mechanisms accounting for ethanol’s effects on nervous system development include perturbed fibroblast growth factor (Fgf) and Sonic hedgehog (Shh) signaling. In zebrafish, forebrain GABAergic neuron development is dependent on Fgf19 and Shh signaling. The present study was conducted to test the hypothesis that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
118
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(130 citation statements)
references
References 79 publications
10
118
2
Order By: Relevance
“…However, there are significant differences between embryo and embryo + extraembryonic fluid as well as between the two time points of embryos in individual genetic backgrounds. While these results are consistent with the ethanol concentration determined by other groups (Flentke, Klinger, Tanguay, Carvan, & Smith, 2014; Reimers, Flockton, et al, 2004; Zhang et al, 2013), these data suggest that there are two levels of barriers to full ethanol equilibrium with the media. The first is at the level of the chorion, while the second is set up between the embryo and the extraembryonic fluid.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…However, there are significant differences between embryo and embryo + extraembryonic fluid as well as between the two time points of embryos in individual genetic backgrounds. While these results are consistent with the ethanol concentration determined by other groups (Flentke, Klinger, Tanguay, Carvan, & Smith, 2014; Reimers, Flockton, et al, 2004; Zhang et al, 2013), these data suggest that there are two levels of barriers to full ethanol equilibrium with the media. The first is at the level of the chorion, while the second is set up between the embryo and the extraembryonic fluid.…”
Section: Resultssupporting
confidence: 91%
“…Zebrafish have been used to examine the teratogenic effects of ethanol (Ali, Champagne, Alia, & Richardson, 2011; Bilotta, Barnett, Hancock, & Saszik, 2004; Blader & Strähle, 1998; Dlugos & Rabin, 2003; Gerlai, Lahav, Gou, & Rosenthal, 2000; Gerlai, Lee, & Blaser, 2006; Li et al, 2007; Lockwood, Bjerke, Kobayashi, & Guo, 2004; McCarthy et al, 2013; Pan, Chatterjee, & Gerlai, 2012; Reimers, Flockton, & Tanguay, 2004; Stockard, 1910; Zhang, Ojiaku, & Cole, 2013; Zhang, Turton, Mackinnon, Sulik, & Cole, 2011). However, there is a lack of consensus regarding ethanol treatment regimens and how these regimens would relate to humans.…”
Section: Introductionmentioning
confidence: 99%
“…28 Our group used Headspace Gas Chromatography and found tissue levels to be *24%-37%, depending upon the age of the embryo, with older embryos having lower tissue levels. 29 One possible reason for the early disagreement in tissue levels of ethanol may be the very rapid rate at which ethanol levels equilibrate, [28][29][30][31] and therefore, extended or multiple washes would result in an underestimation of the ethanol concentration. Collectively, these studies indicate that the use of ethanol concentrations at or above 2% in the media is likely to result in suprapharmacological levels of ethanol.…”
Section: Models Of Fasd: Return Of the Fishmentioning
confidence: 99%
“…78 Work in chicken, mouse, and zebrafish has shown that ethanol exposure reduces Shh signaling leading to increased CNCC death, as well as disrupted midline and eye development. 30,[79][80][81][82] These ethanol-induced phenotypes can be rescued by injection of shh mRNA. 50 In addition to altering retinoic acid signaling, one alternative (or additional) mechanism by which ethanol attenuates Shh is the disruption of cholesterol modification of Shh needed for proper signaling, as has been found in zebrafish.…”
Section: Zebrafish Models Of Fasdmentioning
confidence: 99%
See 1 more Smart Citation